PENGELOMOKKAN DATA MENGGUNAKAN JACKKNIFE RESAMPLING DENGAN UKURAN PUSAT MEAN, MEDIAN DAN KUARTIL - Stephen Christian; Tony Tony; Dyah Erny Herwindiati (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Applications grouping data with a simple measuring devices using Jackknife method is an application used to classify an arbitrary multivariate data and image data using the Jackknife method to measure the value of the center of the mean, median and first quartile. Based on the results of tests performed, the application is successful menyedikan every size value calculation results center mean, median and first quartile in graphical form.  Kata Kunci: Jackknife, Kuartil pertama, Mean, Median, Pengelompokkan Data